Residential interior design : a guide to planning spaces - Mitton, Maureen; Nystuen, Courtney (Hoboken, N.J. : J. Wiley, 2011)
"The only introduction to residential interior design focusing on space planning, Residential Interior Design goes beyond decorating books to uncover the relationship of interior design to the totality of the architectural environment. This one-stop reference supplies the basic information every designer needs to plan specific rooms. Accessbility and related building codes are considered in tandem with human factors and dimensions of fixtures and furnishings, all reflecting good design practice. With expanded coverage of building styles, systems, and sustainability, Residentail Interior Design is sure to remain an essential basic reference"--
"The only introduction to residential interior design focusing on space planning, Residential Interior Design goes beyond decorating books to uncover the relationship of interior design to the totality of the architectural environement. This one-stop reference supplies the basic informaiton the designer needs to plan specific rooms and deals with the issues that a the designer will likely encounter. Accessbility and related building codes are considered in tandem with human factors and dimensions of fixtures and furnishings, all reflecting good design practice"--
Includes bibliographical references and index.
Keywords: Interior architecture; Dwellings -- Planning; Dwellings -- Specifications; ARCHITECTURE / Interior Design / General